2017
DOI: 10.15208/beh.2017.09
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the impact of select macroeconomic variables on the Indian Stock Market: A heteroscedastic cointegration approach

Naushad Alam

Abstract: The present study examines the impact of the macroeconomic variables on the stock prices in India. To fulfil the objective of the study monthly data of inflation, short-term interest rate, long-term interest rate, index of industrial production, exchange rate, money supply, and the stock indices of CNX Nifty and BSE SENSEX were collected from March 2005 to April 2013. Heteroscedastic cointegration approach was employed using a Johansen test of cointegration, OLS and GARCH (1, 1) model to find out the long-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
1
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 13 publications
3
10
1
5
Order By: Relevance
“…Lagged IR is insignificant in explaining stock prices for the majority of the sampled countries. While this is similar to the Mexican evidence presented by Abugri (2008), it runs counter to prior studies such as Alam (2017) in the context of the Indian markets.…”
Section: Ircontrasting
confidence: 77%
See 4 more Smart Citations
“…Lagged IR is insignificant in explaining stock prices for the majority of the sampled countries. While this is similar to the Mexican evidence presented by Abugri (2008), it runs counter to prior studies such as Alam (2017) in the context of the Indian markets.…”
Section: Ircontrasting
confidence: 77%
“…Studies by Humpe and Macmillian (2009), Adam and Tweneboah (2008), Hussain et al (2013) and Alam (2017) found that interest rates may negatively affect stock prices both directly and indirectly. Peiró (2016) considered the cases of France, Germany and UK and reported that interest rates are key factors in determining stock returns in the short run (but not in the long term) across all countries.…”
Section: Interest Ratesmentioning
confidence: 99%
See 3 more Smart Citations